BRIDGING CURRICULUM AND COMPETENCY: OBE-BASED TEACHING MATERIAL DEVELOPMENT FOR 21ST-CENTURY ISLAMIC TEACHER EDUCATION - Mohone Mohone; Supiah Budiono; Lamsike Pateda (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study addresses the critical gap in the availability of teaching materials aligned with the Outcome-Based Education (OBE) framework within the Indonesian Language and Literature Learning Development course for Islamic Education Management. In the context of 21st-century educational demands, OBE emphasizes measurable learning outcomes, competency development, and the integration of relevant, future-oriented pedagogical practices. To bridge the disconnect between curriculum design and competency achievement, this research developed and validated OBE-based teaching materials using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model through a mixed-methods Research and Development (R&D) approach. Data were collected from lecturers and students of the Islamic Education Management at IAIN Gorontalo via curriculum document analysis, interviews, observations, expert validation sheets, user response questionnaires, and learning outcome assessments. Quantitative analysis employed eligibility percentages and N-Gain calculations to evaluate material validity, practicality, and effectiveness. Results indicate that the developed materials are valid (expert validation >80%), practical (>80% positive user feedback), and effective (significant improvement in student learning outcomes, as evidenced by N-Gain scores). This study demonstrates that systematically designed OBE-based teaching materials not only enhance curriculum relevance but also strengthen the professional competencies of prospective Islamic educators. The findings offer a replicable model for curriculum innovation in Islamic higher education, supporting the development of adaptive, competitive, and results-driven teacher education programs aligned with global educational standards.